Teachers Use of Tools for Student Success: Challenging Learning Behaviors - Murry, Francie R (Advances in Social Sciences Research Journal, 2018)
This study investigated the impact teacher’s use of two tools on the social and academic behaviors of twenty middle school students. The general education teachers described the students as assignment incompleters but bright enough to complete work. These students were at risk for failing the majority of their classes in the first semester and were being considered for interventions at the third tier of the Response to Intervention (RTI) model. Four research questions were identified to explore the use of the 9-Grid tool for teachers’ use in the identification of needed assignment adaptations and the RAFT to implement the assignment differentiation. Both tools were used in the content areas of music, mathematics, history, science, and physical education over a 6-week period. Results indicated that students increased in both social and academic behaviors after teachers implemented their use of the 9-Grid and the RAFT.